Median Nerve Injury Caused by Screw Malpositioning in Percutaneous Scaphoid Fracture Fixation - Marta Starnoni, MD; Giulia Colzani, MD; Giorgio De Santis, MD; Andrea Leti Acciaro, MD (Plastic and Reconstructive Surgery, Global Open, 2019)
Summary:. An unusual complication of percutaneous fixation of a schapoid fracture in a 36-year-old man is described. After this surgery, the patient complained of numbness and tingling within the median nerve distribution and thenar weakness. An Electromyography showing moderate CTS had led to carpal tunnel decompression, which resulted unsuccessful. When the patient presented to us, both sensory and motor median nerve impairment were present, interfering with his professional activity. A computed tomography scan performed to assess the scaphoid screw position, showed that the screw had been placed volar to the scaphoid, adjacent to the median nerve. Surgery confirmed median nerve compression by the screw, especially during complete wrist extension. The surgical removal of the screw led to immediate improvement of both the motor and sensory functions of the nerve, with complete clinical restoration of nerve function and resolution of the symptoms 2 months postoperatively.